مساهمة منهج التربية الإسلامية في تنمية الذكاءات المتعددة من وجهة نظر طلاب المرحلة المتوسطة في محافظة الأحمدي بدولة الكويت: The Contribution of The Islamic Education Curriculum to The Development of Multiple Intelligences from The Viewpoint of Middle School Students in Ahmadi Governorate in The State of Kuwait - Adel Talal Alfadhli, Sarah; Mohamed Adnan, Mohamed Azrien; Wan Mokhtar, Wan Rohani (Journal Al-Muqaddimah, 2023)
This study aims to identify the extent to which the contribution of the Islamic education curriculum to the development of multiple intelligences from the point of view of middle school students in the governorate of Ahmadi, Kuwait. The study population consisted of Female students of Baraka Bint Al-Numan school, and male students of Mubarak Abdullah Al-Jaber School in Kuwait. A qualitative and quantitative methods approach was used in this study, in which the researchers used a convenience sampling method to select the study sample. The study population consisted of 350 male and female students. A total of 322 questionnaires were successfully collected for analysis. Questionnaire was used as a tool to collect data which consisted of 33 items. To obtain the results of this study, descriptive analysis, independent sample t-test and one -way ANOVA were used. The study concluded as follows: 1) The Islamic education curriculum contributes to the development of multiple intelligences from the point of view of middle school students in the Ahmadi Governorate in the State of Kuwait. 2) There is a statistically significant difference at 0.05 level between the study sample on the contribution of Islamic Education Book content in the development of multiple intelligences of grade and cumulative average, except gender. 3) There is no statistically significant difference at 0.05 level between the study sample on the contribution on contribution of teachers in the development of multiple intelligenceson personality variables (gender, grade, and cumulative average). 4) There is no statistically significant difference at 0.05 level between the study sample on the contribution of educational activities in the development of multiple intelligenceson on gender and cumulative rate except for grade.